PROBLEMATIKA TANAH RESTAN DI DESA BANJAR PANJANG KECAMATAN KERUMUTAN TAHUN 2020-2021 - Ilma Zukhruf Annisa; Erman M (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study found that the management of restan land in Banjar anjang Village, Kerumutan Subdistrict, is still not going well, because the implementation is still being used for personal gain by planting palm oil on restan land and village treasury land, various inhibiting factors that cause non-management of treasury land assets villages both administratively, planning and utilization, including: There are no village officials who have the appropriate background in the field of asset management both knowledge, expertise in finance and reporting, as well as the status of land titles that are still unclear, so that village treasury land assets what should be village income and used for the public interest is managed by the community privately. This research use desciptive qualitative approach. This research was conducted in Banjar Panjang Village, Kerumutan District, Pelalawan Regency and the Office of Manpower and Transmigration. The data used in this study were primary and secondary data, and the informants in this study were the Head of the Manpower and ransmigration Office, the Head of Banjar Panjang Village, the Secretary of Banjar Panjang Village, the Head of Community Welfare Affairs in Banjar Panjang Village, the Chairperson of the Village Tas Land Management, Head of Restan Land Management and Community Leader of Banjar Panjang Village. This study uses the theoretical framework of policy implementation according to Van Meter and Van Horn theory The results of this study indicate that the implementation of the policy on the use of restan land in the village of Banjar Panjang has not been carried out. It can be seen from the Van Meter and Van Horn Indicators 1) standard and policy objectives that the policy targets related to Restan Land are intended for residents of the KK fraction. 2) Resources, HR who do not have expertise in the land sector, inadequate facilities and infrastructure in matters of asset management. 3) the character of the organization, the government of Banjar Panjang Village, Kerumutan District, Pelalawan Regency, the division of tasks is not in accordance with the duties and functions of each agency. 4) the attitude of local government implementation is considered that the commitment or support for the implementation of this program is good enough that village land, especially restan land, is allocated for family members and residents who need it. 5) communication between communication organizations is one of the factors that hinders the implementation of the policy on the use of restan land in Banjar Panjang Village, Kerumutan District, Regency. 6) the social, economic, social and political environment in this persuasive process received a lot of resistance from the public. Keywords: problematic, Restan Land. Transmigration